A Systematic Review to Examine Barriers and Facilitators to Seeking Mental Health Services Among University/College Students in the United States - Zainab S. Almogheer; Sarret Seng; Donna L. Schuman; Mary Kay Rayens; Debra Moser; Chizimuzo T. C. Okoli (Journal of the American Psychiatric Nurses Association, 2026)
Background: University/college students experiencing mental health conditions often face barriers that limit their willingness to seek help. Conversely, some students may view their mental health conditions as facilitators to use available mental health services. Aim: This review explores barriers and facilitators to mental health help-seeking among college students. Methods: A systematic review of published data-based papers. This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, using three databases: Cumulative Index to Nursing and Allied Health, PubMed, and PsycINFO. The review examined articles from May 2013 until May 2025, specifically selecting articles addressing barriers and facilitators to mental health help-seeking among university/college students. Results: A total of 31 studies were included in the final analysis. Key barriers encompassed stigma, logistical barriers, and cultural issues. Conversely, person-related factors, a history of mental health problems, and positive experiences with mental health services emerged as facilitators for the use of mental health services. Conclusions: It is important to understand the impact of cultural disparities and personal beliefs on mental health, underscoring the significance of normalizing the recognition of mental health concerns and seeking mental health services among university/college students. It is imperative to develop interventions that facilitate students’ involvement in professional mental health help-seeking within the university/college context.